Nivolumab for previously treated unresectable metastatic anal cancer (NCI9673): a multicentre, single-arm, phase 2 study. Issue 4 (April 2017) - Morris, Van K; Salem, Mohamed E; Nimeiri, Halla; Iqbal, Syma; Singh, Preet; Ciombor, Kristen; Polite, Blase; Deming, Dustin; Chan, Emily; Wade, James L; Xiao, Lianchun; Bekaii-Saab, Tanios; et al.
Summary: Background: Squamous cell carcinoma of the anal canal (SCCA) is a rare malignancy associated with infection by human papillomavirus (HPV). No consensus treatment approach exists for the treatment of metastatic disease. Because intratumoral HPV oncoproteins upregulate immune checkpoint proteins such as PD-1 to evade immune-mediated cytotoxicity, we did a trial of the anti-PD-1 antibody nivolumab for patients with metastatic SCCA. Methods: We did this single-arm, multicentre, phase 2 trial at ten academic centres in the USA. We enrolled patients with treatment-refractory metastatic SCCA, who were given nivolumab every 2 weeks (3 mg/kg). The primary endpoint was response according to Response Evaluation Criteria in Solid Tumors, version 1.1, in the intention-to-treat population. At the time of data cutoff, the study was ongoing, with patients continuing to receive treatment. The study is registered withClinicalTrials.gov, numberNCT02314169 . Results: We screened 39 patients, of whom 37 were enrolled and received at least one dose of nivolumab. Among the 37 patients, nine (24% [95% CI 15–33]) had responses. There were two complete responses and seven partial responses. Grade 3 adverse events were anaemia (n=2), fatigue (n=1), rash (n=1), and hypothyroidism (n=1). No serious adverse events were reported. Interpretation: To our knowledge, this is the first completed phase 2 trial of immunotherapy for SCCA. Nivolumab is well tolerated and effective as a monotherapy for patients with metastatic SCCA. Immune checkpoint blockade appears to be a promising approach for patients with this orphan disease. Funding: National Cancer Institute/Cancer Therapy Evaluation Program, the HPV and Anal Cancer Foundation, the E B Anal Cancer Fund, The University of Texas MD Anderson Moon Shots Program, and an anonymous philanthropic donor.